2016
DOI: 10.1111/head.12760
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Pilot Trial of Behavioral Insomnia Treatment for Chronic Migraine With Comorbid Insomnia

Abstract: Behavioral treatment of comorbid insomnia in individuals with CM produced large reductions in headache frequency, though some improvement in headache occurred with a behavioral intervention not focused on modifying sleep. Among the CBTi group only, both headache frequency and sleep parameters continued to improve after treatment, suggesting the presence of enduring effects over time. Directly treating insomnia using components of stimulus control and sleep restriction holds promise for reducing comorbid migrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 60 publications
3
65
1
8
Order By: Relevance
“…60 Similarly, in individuals with CM, behavioral treatment of comorbid insomnia yielded reductions in headache frequency. 53 These findings are interesting, albeit limited in number and scope, and underscore a need for additional, larger studies for confirmation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…60 Similarly, in individuals with CM, behavioral treatment of comorbid insomnia yielded reductions in headache frequency. 53 These findings are interesting, albeit limited in number and scope, and underscore a need for additional, larger studies for confirmation.…”
Section: Discussionmentioning
confidence: 94%
“…52 Objective sleep data such as polysomnography are often not feasible for research due to cost and reactivity to test conditions or “first night effect.” Actigraphy was utilized recently in an outcome study of Cognitive behavioral therapy for insomnia (CBTi) in migraine. 53 Wearable accelerometers are inexpensive and increasingly widely available, and can represent sleep/wake cycles in normal sleepers with an accuracy that approximates actigraphy; however, they lack accuracy in determining sleep/wake cycles in clinical populations and correlate poorly with sleep stages documented in polysomnography. 54 Thus, the current standard of care in diagnosis of insomnia in the clinical setting is prospective sleep diaries and validated questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…19 Treatment of insomnia in migraine patients with CBT for insomnia shows significant benefit in sleep efficiency (as measured by actigraphy) as well as reductions in headache frequency. 37 Sleep disturbances may be the manifestation of a common shared biology in at least a subset of patients with migraine, so should be screened and addressed.…”
Section: Sleep Disorders and Their Relationship To Migrainementioning
confidence: 99%
“…[3][4][5] Migraineurs frequently report poor sleep quality, which is associated with increased migraine frequency and severity. [13][14][15] The relationship may be bi-directional, however. A recent study reported that patients with insomnia had a higher prevalence of migraine than did patients without insomnia; interestingly, patients with migraine who had insomnia reported more headache-related disability (as measured by the Headache Impact Test [HIT-6]) than patients with migraine but without insomnia.…”
Section: Introductionmentioning
confidence: 99%